Challenges and Opportunities in Cooperatives Development in Nepal - Joshi, Janak Raj (Journal of Durgalaxmi, 2024)
This research investigates the challenges and opportunities in the evolution of cooperatives in Nepal. Using a mixed-method approach grounded in secondary material and thematic analysis, the study explores the historical background, present situation, and future directions of the cooperative movement in Nepal. Key findings highlight significant problems such as insufficient legal frameworks, poor access to capital, governance concerns, and a lack of professional management. Simultaneously, the study identifies opportunities in areas like financial inclusion, women's empowerment, rural development potential, and support for sustainable economic growth. Recommendations for legislators, cooperative leaders, and stakeholders include enhancing governance and management practices, improving financial sustainability, strengthening the regulatory framework, promoting technology adoption, fostering innovation and diversification, and aligning cooperative strategies with national sustainable development goals. These measures aim to bolster cooperatives' contributions to Nepal's socioeconomic growth.